Scripture matters for sustainable whole-person nursing - Diane McCroskey (Health for All Nations, 2022)
Nursing is truly an ever-evolving profession. It is one of the most versatile occupations within the health care arena. It is not the same profession today as it was years ago. Nurses need direction to create order out of chaos in today's complex multifaceted healthcare environment. My survival plan entails a personal relationship with Christ which is strengthened by consistent time spent in the Holy Scriptures. Reading the Bible daily and studying scripture is a necessity. Scripture passages can inspire nurses particularly in going forward, in endlessly caring for other individuals and in sharing our passion to serve others as we venture forth.